Improving the Ability to Write Natural Number Symbols (1-9) Through the Finger Numbers Media Board for Down Syndrome Students - Gustia Sepriani Putri; Damri Damri; Mega Iswari; Grahita Kusumastuti; Antoni Tsaputra (Edumaspul: Jurnal Pendidikan, 2024)
The background to the implementation of this research was because it was found that a student with Down syndrome in class I SLB N 1 Alahan Panjang was unable to write natural number symbols (1-9) in phase A mathematics learning. The aim of this research was to prove the use of the finger numbers board media in improve the ability to write natural number symbols (1-9) for class I Down syndrome students at SLB N 1 Alahan Panjang. The research method used in this research is an experimental method with a single subject approach or Single Subject Research (SSR). This study used an A-B design consisting of two conditions, namely baseline (A) and intervention (B). The use of the A-B design was adapted to the aim of only seeing an increase in students' abilities when using the finger numbers board media. The results of the research showed that the ability to write natural number symbols (1-9) of students in the baseline condition (A) was obtained at a percentage of 59.25%, 59.25%, 59.25%, 59.25%, 59.25%. In intervention (B) 66.67%, 81.49%, 81.49%, 81.49%, 88.89%, 88.89%, 88.89%, 88.89%, 88.89%, 92.60%. Based on this data, students' ability to write natural number symbols (1-9) increases.